Robust beamformer design against mismatch in microphone characteristics and acoustic environment - Nahma, L.; Dam, Hai Huyen Heidi; Nordholm, Sven (2018)
© 2018 IEEE. Broadband beamformers are known to be sensitive not only to mismatches in microphone characteristics but also in the acoustic environment. In this work, we propose a robust broadband beamformer design using weighted least square optimization technique, which takes into account the room reverberation as well as the mismatches in microphone gain and phase characteristics. The robust design procedure optimize the mean performance of the beamformer with the room impulse response estimated using the image source method. Design examples demonstrate performance improvement in terms of significant reduction in error sensitivity for the robust design formulation.